(untitled) (Journal of Global Accounting, 2023)
The paper aims to clarify the relationship between financial distress and corporate profitability from a developing country context. Financial distress was proxied using the Z score developed by Altman (1968); while, the profitability indices were Return on Assets (ROA), Gross Profit Margin (GPM), Return on Equity (ROE) and Net Profit Margin (NPM). The study used the ex-post facto research design. The sample comprised all quoted consumer goods manufacturing firms listed on the Nigerian Stock Exchange (NSE) as at December, 2017. The study used secondary data; obtained from annual reports and accounts of the studied companies. The study employed Panel Estimated Generalised Least Squares, using cross-sectional weighting to validate the hypotheses. Firm size and leverage were included in the model as control variables. The study documents mixed findings; financial distress had a positive significant effect on return on assets; but, a negative significant effect on gross profit margin. The effect on return on equity and net profit margin were positive but non-significant.